2016
DOI: 10.2903/j.efsa.2016.4654
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure assessment to Alternaria toxins in the European population

Abstract: Alternaria toxins are secondary metabolites produced by fungi that can contaminate cereals, oilseeds, fruits and vegetables. The chronic dietary exposure to four individual Alternaria toxins was estimated using 15,563 analytical results/4,249 samples (3,648 on alternariol (AOH), 3,654 on alternariol monomethyl ether (AME), 4,168 on tenuazonic acid (TeA) and 4,093 on tentoxin (TEN)). Most of the analytical results were left‐censored data (92%), with only 1,290 quantified results (mainly on ‘Oilseeds’ and ‘Grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 19 publications
1
114
0
3
Order By: Relevance
“…For instance, in a recent food survey AOH was measured in sunflower seed oil, wheat flour and tomato sauce at median concentrations of 1.2, 2.1, and 6.6 µg kg –1 , respectively . With regard to the estimated daily dietary intake of 1.0–15.2 ng kg –1 bw the observed inducing effects of AOH on IL‐8 transcription and secretion at concentrations of 0.02 and 0.2 µ m , respectively, need to be further investigated. These concentrations can be considered as physiologically relevant and immuno‐stimulating properties of AOH have not been described yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a recent food survey AOH was measured in sunflower seed oil, wheat flour and tomato sauce at median concentrations of 1.2, 2.1, and 6.6 µg kg –1 , respectively . With regard to the estimated daily dietary intake of 1.0–15.2 ng kg –1 bw the observed inducing effects of AOH on IL‐8 transcription and secretion at concentrations of 0.02 and 0.2 µ m , respectively, need to be further investigated. These concentrations can be considered as physiologically relevant and immuno‐stimulating properties of AOH have not been described yet.…”
Section: Discussionmentioning
confidence: 99%
“…The European Food Safety Authority (EFSA) estimated the daily dietary intake of AOH to be low (1.0–15.2 ng kg –1 bodyweight (bw)), but nevertheless to exceed presumably the threshold of toxicological concern (TTC) of 2.5 ng kg –1 bw per day by far. A more detailed hazard characterization for AOH was, hence, demanded …”
Section: Introductionmentioning
confidence: 99%
“…per day for adults by far exceeds the threshold of toxicological concern (TTC) value for AOH (2.5 ng/kg b.w. per day) (EFSA 2011, 2016). Consequently, EFSA emphasized the necessity of additional data to characterise a potential hazard arising from AOH exposure (EFSA 2016).…”
Section: Introductionmentioning
confidence: 99%
“…per day) (EFSA 2011, 2016). Consequently, EFSA emphasized the necessity of additional data to characterise a potential hazard arising from AOH exposure (EFSA 2016). Moreover, recent studies reported AOH to exhibit immunosuppressive properties in vitro by modifying the expression of CD receptors and proinflammatory cytokines (Grover and Lawrence 2017; Solhaug et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are still no international regulations for any of the Alternaria mycotoxins in food and feed, the European Food Safety Authority (EFSA) recently highlighted that the major contribution of Alternaria spp. toxins to the diet is due to consumption of tomato and tomato‐based products …”
Section: Introductionmentioning
confidence: 99%